xét n ⋮ 2 => n(5n + 3) ⋮ 2
xét n không chia hết cho 2 => n = 2k + 1
=> n(5n + 3) = (2k + 1)[5(2k + 1) + 3)
= (2k + 1)(10k + 8)
= 2(5k + 4)(2k + 1) ⋮ 2
vậy với mọi n nguyên thì n(5n + 3) ⋮ 2
Đặt A = n . (5n + 3 )
TH1 : n là số chẵn
\(\Rightarrow\)n = 2k ( k \(\in Z\))
Khi đó ta có : A = 2k . (5 . 2k +3 ) \(⋮2\)
TH2 : n là số lẻ
\(\Rightarrow\)n = 2b + 1
Khi đó ta có : A = (2b + 1) . [ 5 .(2b + 1 ) + 3 ]
A = (2b+1) . ( 10b + 5 + 3 )
A = (2b + 1) . (10b + 8)
A = (2b + 1 ) . 2 . (5b + 4) \(⋮2\)
Vậy với mọi n thuộc Z ta luôn có n . (5n + 3 ) \(⋮2\)\(\rightarrowĐPCM\)
#HOK TỐT #